Dose-Effect Relationship of Chitosan and Danshen Combined Injection for Fallopian Tube Recanalization - Huang, Chen; Wu, Qiong; Liang, Jiabin; Wang, Qian; He, Xueping; Xie, Yanqiu; Lu, Yanbing; Su, Jianfen; Tang, Yutuan (Frontiers in Pharmacology, 2022)
Objectives: This study examined the dose-effect relationship of chitosan and danshen combined injections on the long-term prevention of fallopian tube re-obstructions, with increased pregnancy rates in infertile women. Methods: High-performance liquid chromatography was used to determine the content changes of combined chitosan and danshen injection. Two hundred and eighty patients with fallopian tube obstructions were randomly assigned to four groups. Group A (control group, saline), Group B (2 ml chitosan, 4 ml danshen), Group C (2 ml chitosan, 10 ml danshen), and Group D (1 ml chitosan, 10 ml danshen). Injections were administered after tubal recanalization. Results: The effective constituent of chitosan and danshen injection was stable. Tubal patency rate was 94.2% and 87.3% in Group C after 1 and 3 years, respectively, which was significantly higher than Groups A (38.6%, 31.5%), B (73.5%, 64.1%), and D (68.5%, 50.7%). Intrauterine pregnancy rates were 61.8% and 79.4% in Group C after 1 and 3 years, respectively, and were significantly higher than Groups A (31.8%, 34.8%), B (40.1%, 62.5%), and D (38.5%, 58.5%) (p < 0.05). Conclusion: Combined Chitosan and danshen injections prevented tubal obstruction and increased pregnancy rates for long periods using an optimal ratio of 1 part chitosan and 5 parts danshen.